PROUNI: trajetórias - Ferreira, Karin Terrell (2011)
Established in 2004 by the Federal Government and ruled by Ministry of Education as a public policy of educational inclusion, the Program Universidade para Todos (ProUni) aims to help the modification of the exculpatory reality of higher education in Brazil. By granting scholarships to low-income students - especially those from public schools in the country - the Program provides the entry of these young people in private higher institutions, previously registered, which in turn have tax benefits. Under this Program, a few years ago, the presence of social categories that were practically excluded from higher education raises questions that deserve reflection. Studying the story of these students during their initial training and trying to understand the changes in demands and in daily practices at school and labor market, as well as the profile of these students in contemporary society, represents a necessity for research and for the educational policies in Brazil. Through this new reality of Brazilian education, this work has the intention of investigate the factors that motivate students who enrolled in the Pedagogy course at an IES from Limeira/SP to seek the graduation at this kind of teaching, understanding the meaning of the education for them, as well as their expectations and aspirations related to the future and work. This analysis of the scholar and professional trajectories from the students is guided at a sociological perspective of Pierre Bourdieu and contributors.